2021
DOI: 10.3390/foods10020267
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Phenolic Compounds and Triterpene Acids of Twelve Apple (Malus domestica Borkh.) Cultivars

Abstract: Apple (Malus domestica Borkh.), a popular and widely cultivated fruit world-wide, contains bioactive compounds responsible for their health benefits. Here we report the amounts of some bioactive compounds: two major triterpenes (oleanolic and ursolic acids) and polyphenols (phenolic acids, flavan-3-ols, flavonoids and t-resveratrol), together with bioactive properties of twelve apple cultivars measured by chromatographic and spectrophotometric methods. Significant variations were found comparing the bioactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 41 publications
0
25
1
Order By: Relevance
“…The evaluation of the dynamics of the composition of phenolic compounds between the individual parts of ‘Galaval’ apples showed that in apple peel samples, differently from apple flesh samples, flavonols predominated, their percentage distribution ranging from 24% to 58% of the total amount of the identified and quantified phenolic compounds ( Figure 6 , Panel b). Geana et al found that flavonols and anthocyanins were usually found in apple peel, while flavan-3-ols, dihydrochalcones, and hydroxycinnamic acids were the major polyphenol groups found in apple flesh [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of the dynamics of the composition of phenolic compounds between the individual parts of ‘Galaval’ apples showed that in apple peel samples, differently from apple flesh samples, flavonols predominated, their percentage distribution ranging from 24% to 58% of the total amount of the identified and quantified phenolic compounds ( Figure 6 , Panel b). Geana et al found that flavonols and anthocyanins were usually found in apple peel, while flavan-3-ols, dihydrochalcones, and hydroxycinnamic acids were the major polyphenol groups found in apple flesh [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Feng et al estimated that chlorogenic acid has stronger antioxidant properties than quercetin, gallic acid, or α-tocopherol, but its antioxidant activity is weaker than that of rutin [ 61 ]. Flavan-3-ol group compounds, such as procyanidin B1, have been shown to have anti-Alzheimer’s effects [ 62 ], (−)-epicatechin offers benefits regarding renal alterations associated with inflammatory or metabolic diseases and increased muscle growth and strength [ 48 , 63 ], and (+)-catechin has anti-obesity effects [ 64 ]. Procyanidin B1, (+)-catechin, and (−)-epicatechin are the main compounds in apples responsible for reducing cholesterol levels [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, when raw materials rich in polyphenols are macerated, the polyphenols extraction yield is also higher in apple juice and then in cider. Apples, namely apple peels, present antioxidant activity [124] directly related to the abundance of phenolic compounds [125]. The antioxidant activity of the cider obtained by maceration is higher compared to the cider without the maceration stage.…”
Section: Changes In Sensory Volatile and Phenolic Profiles During Cider Processingmentioning
confidence: 99%
“…In addition to its low-calorie levels and high levels of water and fiber, containing essential vitamins, minerals, and trace elements makes the apple a healthy fast food. Phenols, pectin, sugar, acids, and antioxidants containing in apples generally have positive effects on human health [2][3][4]. Some diseases such as cancer, cardiovascular disease, asthma, and diabetes can be prevented through some biochemical compounds of apple [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%